Nuclear lipid droplets derive from a lipoprotein precursor and regulate phosphatidylcholine synthesis - Kamil Sołtysik (Nature Portfolio, 2019)
The origin and physiological significance of lipid droplets (LDs) in the nucleus is not clear. Here authors show that nucleoplasmic LDs in hepatocytes are derived from apolipoprotein B (ApoB)-free lumenal LDs and constitute a feedback mechanism to regulate PC synthesis in accordance with ER stress.